New Chimeric Antigen Receptor Design for Solid Tumors - Yuedi Wang; Yuedi Wang; Feifei Luo; Feifei Luo; Jiao Yang; Jiao Yang; Chujun Zhao; Yiwei Chu; Yiwei Chu (Frontiers in Immunology, 2017)
In recent years, chimeric antigen receptor (CAR) T-cell therapy has become popular in immunotherapy, particularly after its tremendous success in the treatment of lineage-restricted hematologic cancers. However, the application of CAR T-cell therapy for solid tumors has not reached its full potential because of the lack of specific tumor antigens and inhibitory factors in suppressive tumor microenvironment (TME) (e.g., programmed death ligand-1, myeloid-derived suppressor cells, and transforming growth factor-β). In this review, we include some limitations in CAR design, such as tumor heterogeneity, indefinite spatial distance between CAR T-cell and its target cell, and suppressive TME. We also summarize some new approaches to overcome these hurdles, including targeting neoantigens and/or multiple antigens at once and depleting some inhibitory factors.